Design and Application Of Materials and Tools Work At PT. Dwi Karya Prasetya Nusantara - Larasati, Rani Mei Clara; Hariadi, Bambang; Sulistiowati, Sulis (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
During this time in doing receipt of customer orders, PT Dwi Prasetya Nusantara Works still experienced constraints because there is no regulatory process in the reduction of the amount of the stock tools of work and material. Method of SDLC (System Development Life Cycle) is required to create an application setting materials and tools work-based websites that can help sales manager to perform acceptance customer orders accurately and quickly. Applications can provide information about the materials and work tools data, and can deliver results in the form of the report results.By using this application, the sales manager can accelerate the process of service especially in performing the acceptance of customer orders.Â